Seasonal and Solar Cycle Dependence of Energy Transfer Rates in the Auroral E‐Region. Issue 12 (25th November 2021) - Zhan, Weijia; Kaeppler, Stephen R.; Reimer, Ashton; Varney, Roger
Abstract: We report one of the first comprehensive ground‐based investigations of energy transfer rates in the E‐region ionosphere compared relative to geomagnetic activity, seasonal effects, and solar activity level using nearly continuously sampled data collected with the Poker Flat Incoherent Scatter Radar (PFISR) between 2010 and 2019. We quantified the integrated electromagnetic (EM) energy transfer rate and the integrated Joule heating rate in the E‐region between 90 and 130 km, which includes the contribution from the neutral winds. We find that (a) the median Joule heating rate and EM energy transfer rate in the evening sector are larger in the winter versus the summer and have similar magnitudes in the spring and fall for the same solar activity and geomagnetic conditions. (b) The seasonal dependence of the energy transfer rates is closely associated with the seasonal variations of the electric fields. Our analysis shows that the larger EM energy transfer and Joule heating rates in disturbed conditions in the winter versus the summer are associated with the combined effects of both the electric field and Pedersen conductance with the electric field playing a dominant role. Given that the Pedersen conductance in the evening sector is closely related to the particle precipitation and field aligned currents in the auroral region, this study provides complementary ionospheric evidence of the winter‐summer asymmetry of the intensity and density of field‐aligned currents (e.g., Ohtani et al.,  2009, https://doi.org/10.1029/2009ja014115 ). (c) The geomagnetic activity level has the most significant impact on the magnitude of the energy transfer rates, followed by seasonal variations, and last the solar activity level. Plain Language Summary: We reported a comprehensive statistical study of energy transfer rates (EM transfer rate and Joule heating rate) in the auroral E‐region in aspects of season, geomagnetic activity, and solar activity. This study is done by collecting ground‐based 10 years of measurements from Poker Flat Incoherent Scatter Radar. We find a consistent seasonal variation of energy transfer rates for different geomagnetic and solar activity levels. That is the EM energy transfer and Joule heating experience larger enhancements in the evening sector in the winter versus the summer and show similar magnitudes in the spring and fall equinoxes. We further find that the seasonal variation of the enhancement is mainly associated with the seasonal variation of the electric field while the seasonal variation of the E‐region conductance could also play a smaller role during disturbed conditions. We also compared the relative importance of season, geomagnetic, and solar activity levels in impacting the energy transfer rates and find that the geomagnetic activity has the largest impact, followed by season and solar activity. Key Points: Geomagnetic activity, seasonal, and solar activity variability of the integrated energy transfer rates are quantified in the E‐region between 90 and 130 km spanning 2010–2019 using PFISR observations for the first time The integrated Joule heating and EM energy transfer rates in the evening sector are larger in winter versus summer and have similar magnitudes in spring and fall equinoxes The larger energy transfer rates in winter relative to summer in disturbed conditions are associated with a combination of electric field and Pedersen conductance